2020
DOI: 10.1155/2020/5204158
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Sensor Data Integration for Indoor Positioning in Ambient-Assisted Living Environments

Abstract: A reliable Indoor Positioning System (IPS) is a crucial part of the Ambient-Assisted Living (AAL) concept. The use of Wi-Fi fingerprinting techniques to determine the location of the user, based on the Received Signal Strength Indication (RSSI) mapping, avoids the need to deploy a dedicated positioning infrastructure but comes with its own issues. Heterogeneity of devices and RSSI variability in space and time due to environment changing conditions pose a challenge to positioning systems based on this techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…When the database receives the information, it must first complete the data conversion and transfer it in an XML document. In this process, it is necessary to clarify the information of the minimum synchronization set [15]. e source of this data information is relatively complicated, and it needs to be confirmed to be correct before it can be arranged in a certain order.…”
Section: Data Processing Methods For Multimedia Vocal Music Educationmentioning
confidence: 99%
“…When the database receives the information, it must first complete the data conversion and transfer it in an XML document. In this process, it is necessary to clarify the information of the minimum synchronization set [15]. e source of this data information is relatively complicated, and it needs to be confirmed to be correct before it can be arranged in a certain order.…”
Section: Data Processing Methods For Multimedia Vocal Music Educationmentioning
confidence: 99%
“…It has been suggested that we cannot rely on RSSI alone for indoor localisation in home environments for PD subjects due to shadowing rooms with tight separation [32,35,39]. Sansano et al combine RSSI signals and inertial measurement unit (IMU) data to test the viability of leveraging other sensors in aiding the positioning system to produce a more accurate location estimate [39].…”
Section: Related Workmentioning
confidence: 99%
“…It has been suggested that we cannot rely on RSSI alone for indoor localisation in home environments for PD subjects due to shadowing rooms with tight separation [32,35,39]. Sansano et al combine RSSI signals and inertial measurement unit (IMU) data to test the viability of leveraging other sensors in aiding the positioning system to produce a more accurate location estimate [39]. Classic machine learning approaches such as Random Forest (RF), Artificial Neural Network (ANN), k-Nearest Neighbour (k-NN) are tested, and the result shows that the RF outperforms other methods in tracking a person in indoor environments.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations